Sports programming on Franco’s television: the conquest of quality through innovation - Bonaut Iriarte, Joseba; Ojer Goñi, Teresa (Anàlisi, 2012)
Franco's television programming has not been studied with great detail. We can only highlight the rigorous work of Palacio and Baget who deeply explain the origins of spanish television. In this context, sports programming has gone unnoticed. However, these contents were essential in the development, expansion and modernization of the television during Franco’s regime. The most relevant milestones of this medium were sport telecasts: television premiere in Barcelona (the first broadcast of a Real Madrid and FC Barcelona football match), the connection to the Eurovision network (European Cup’s football matches) or the first midnight telecast (boxing). But aside from these facts, most of the scientific production on the subject has ignored the great importance of this type of programming in the European context and its relevance to consolidate a quality and popular television. This article will explain the role of sports programming in the consolidation of a public television based on innovation and its real values, regardless of their political influence.